ANTIOXIDANT STATUS IN CURCUMIN TREATED RATS IN EXPERIMENTAL MAMMARY CARCINOGENESIS - P. Jalantha; C. Balachandran; N. Pazhanivel (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The present study was carried out to evaluate the effect of curcumin on lipid peroxidation and antioxidant levels in DMBA (7, 12 Diemthyl Benanthracene) induced mammary carcinogenesis in rats. Twenty four Sprague-Dawley rats were equally distributed to control, DMBA, Tamoxifen (Standard drug) and curcumin groups. DMBA group showed significant (P